Mediating Peace through Local Tradition of Cross-Religious Community in Saparua Island, Moluccas - Hasbollah Toisuta; Abidin Wakano; Miftahul Huda (UIN Maulana Malik Ibrahim Malang, 2022)
On Saparua Island in the Moluccas, Indonesia, local tradition guides the interreligious community of Muslims and Christians. Issues relating to people's races, religions, and ethnic backgrounds frequently spark conflict in the community. At the moment, it is working on maintaining and advancing peace. This article presents an investigation into the factors that contribute to religious harmony in communities comprised of members of different faiths. This research was conducted on Saparua Island through observation and interviews with community figures and members of the religious, academic, youth, and female communities. It was hypothesized, and subsequent research confirmed, that the community adheres to the principles of peace and the way of life espoused by the